INSTITUTIONALIZATION PATTERNS IN BREAST CANCER IMMUNOHISTOCHEMISTRY - Galina Yaneva; Tsonka Dimitrova; Dobri Ivanov; Gergana Ingilizova; Sergei Slavov (Peytchinski Publishing, 2022)
Purpose: The objective of the present study is to analyze scientometrically some essential patterns of the dynamic science institutionalization on breast cancer immunohistochemistry and to outline the most significant scientists, journals, scientific institutions conference proceedings in this interdisciplinary field. Material/Methods: In December 2019, a retrospective problem-oriented, title-word based search was performed in Web of Science Core Collection (WoS), MEDLINE and BIOSIS Citation Index (BIOSIS) of Web of Knowledge as well as in Scopus for 2003-2018. The following parameters were comparatively assessed: annual dynamics of publications, author's names, journal titles, scientific institutions, and scientific forums. Results: There were 1187 publications abstracted in WoS, 776 publications abstracted in BIOSIS, 711 publications abstracted in Scopus, and 616 publications abstracted in MEDLINE. There were journal articles in 288 journals abstracted in WoS, in 234 journals abstracted in MEDLINE, in 156 journals abstracted in Scopus, and in 140 journals abstracted in BIOSIS. The most productive authors were David G. Hicks, Rohit Bhargava and Ian O. Ellis. The 'core' journals were Modern Pathology, Laboratory Investigation and Cancer Research. The most influential scientific institutions were the University of Texas System (USA) and the University of Texas MD Anderson Cancer Center (USA). The annual meetings of the US and Canadian Academy of Pathology and the Annual San Antonio Breast Cancer symposia were most attractive to the investigators worldwide. Conclusion:Our comprehensive results could be of interest to breast cancer researchers and clinicians from smaller countries, institutional science managers, and journal editors.